2022
DOI: 10.30541/v51i4iipp.587-606
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Entrepreneurship: Linking With Economic Growth and Employment Generation (A Panel Data Analysis)

Abstract: The need for entrepreneurs for economic development has always been crucial in history because they are the leaders who invent innovative ideas that give spark to economic activities. They are responsible for the combination of factors of production by capital formation, creating employment opportunities, wealth distribution that facilitates development and growth. A well explained definition of entrepreneurship in the words of Wennekers and Thurik (1999) that successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Results also show that institutional quality/governance restricts opportunity-driven entrepreneurship, which opposes the study (Rasool et al, 2012). But Arshed et al (2022a) and Ho and Wang (2007) had shown that better institutions also increase the regulatory compliance cost to the new businesses and innovators.…”
Section: Estimation Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Results also show that institutional quality/governance restricts opportunity-driven entrepreneurship, which opposes the study (Rasool et al, 2012). But Arshed et al (2022a) and Ho and Wang (2007) had shown that better institutions also increase the regulatory compliance cost to the new businesses and innovators.…”
Section: Estimation Resultsmentioning
confidence: 73%
“…Higher education increases the capacity of entrepreneurs to take decisions confidently in a period of uncertainty (Martinez et al, 2010;Jimenez et al, 2015). Rasool et al (2012) used data from 8 Asian countries from 2005 to 2011. They affirmed that higher education leads to improvement-driven entrepreneurship and necessity-driven entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is not certain, though, is whether these policies should disband fossil fuel installations. Recent policies at European and international levels have brought the spotlight on energy transition, but in reality, it represents only a small part of the entire energy system: the share of electricity in the final consumption of energy from RES is only 20% [55]. Most of the investments so far have been addressed to photovoltaic and eolic power generation, which were not able to eradicate fossil fuel production due to scarcity of energy efficiency capacity in power supply.…”
Section: Discussionmentioning
confidence: 99%
“…Inicjatywa GEM przyczyniła się do prowadzenia badań związków i zależności pomiędzy przedsiębiorczością a różnymi ważnymi aspektami gospodarczymi. Zdaniem autorów zdynamizowało to zwłaszcza prowadzenie badań nad korelacją przedsiębiorczości kraju z rozwojem gospodarczym i dobrobytem (Amorós & Cristi, 2011;Rasool, Gulzar, & Naseer, 2012;Wong, Ho, & Autio, 2005).…”
Section: Problem Operacjonalizacji Przedsiębiorczości Krajuunclassified